2017
DOI: 10.15390/eb.2017.5033
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gender on School Administrators and Teachers’ Perceptions of Learning Organization: A Meta-Analysis Study

Abstract: Bu araştırmanın amacı, cinsiyetin okul yöneticilerinin ve öğretmenlerin öğrenen örgüt algıları üzerindeki etkisini ortaya koyan çalışmaların etki büyüklüklerinin birleştirilmesi ve elde edilecek etki büyüklüğünün çalışmaların yayın türü, yapıldığı bölge, eğitim kademesi, ölçek hazırlanma, ölçeklerin geçerlilik-güvenirlik durumu ve araştırmacının cinsiyetine göre farklılık gösterip göstermediğinin meta-analiz yöntemiyle araştırılmasıdır. Alanyazın taramasında konu ile ilgili doktora tezi, yüksek lisans tezi, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Since publications that produce meaningful results are included in the research process and negatively affect the analysis process, it is recommended to detect publication bias before starting the meta-analysis ( Kalkan, 2017 ). The most commonly used method for publication bias is the funnel plot.…”
Section: Resultsmentioning
confidence: 99%
“…Since publications that produce meaningful results are included in the research process and negatively affect the analysis process, it is recommended to detect publication bias before starting the meta-analysis ( Kalkan, 2017 ). The most commonly used method for publication bias is the funnel plot.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers explain that gender plays a fostering role in developing the learning organization environment (Chen et al, 2010; Thomas et al, 2016). Researchers also demonstrated that gender plays a role in strengthening the university level’s learning organization discipline (Kalkan, 2017). Based on the above arguments, our study hypothesis assumes as follows.…”
Section: Gender and Learning Organizationmentioning
confidence: 99%
“…Since the first time the idea of a "learning organization" was introduced, a big effort has been made to conceptualize the structure of a learning organization and it has always been considered important if this concept is applicable to different types of organizations or not. However, it is alarming that although much is known about the learning organizations in the private sector (Akova, Yıldırım, & Bayram, 2018;Budak, 2000;Öneren, 2012;Watkins & Kim, 2018) this concept is much less under researched among both government institutions and higher education institutions (Bilir & Arslan, 2016;Kalkan, 2017). Public institutions are generally considered as places where individuals are allowed to learn in line with the government"s education policies or the organization"s own goals (Bui & Baruch, 2012).…”
Section: Introductionmentioning
confidence: 99%